Strategi Komunikasi Krisis Pertamina Pada Kasus Viral BBM Pertamax Merusak Kendaraan - Bender, George Wilhelm (LPPM Universitas Bina Sarana Informatika, 2024)
ABSTRAKSI Pertamax is one of the flagship fuel products of Pertamina, known for its advantages such as efficient fuel consumption, engine cleaning, and engine protection. However, towards the end of 2024, complaints from users emerged, with many believing that this flagship fuel caused several vehicles to break down due to clogged fuel filters, damaged fuel pumps, and sediment in the tanks. These complaints were shared on social media and went viral. This situation posed a serious threat to the reputation of Pertamax as a product and Pertamina as its producer. Given the impact of this crisis, Pertamina faced a significant challenge in maintaining consumer trust and ensuring the continued success of their product in the market. Therefore, it is not only important to respond quickly to the crisis, but also to implement the right communication strategy. This study aims to understand Pertamina’s communication strategy in responding to the viral crisis involving Pertamax, which was suspected of causing vehicle damage. Through an in-depth analysis of the communication measures taken, this study is expected to provide insights into how large companies manage crises in the digital age, where information spreads rapidly and can significantly affect public perception.